2020
DOI: 10.3233/jpd-202251
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Psychological Distress, Physical Activity, and Symptom Severity in Parkinson’s Disease

Abstract: Background: The ongoing COVID-19 pandemic has many consequences for people with Parkinson’s disease (PD). Social distancing measures complicate regular care and result in lifestyle changes, which may indirectly cause psychological stress and worsening of PD symptoms. Objective: To assess whether the COVID-19 pandemic was associated with increased psychological distress and decreased physical activity in PD, how these changes related to PD motor and non-motor symptom severity, and what frequency and burden of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
175
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(192 citation statements)
references
References 41 publications
(48 reference statements)
11
175
4
2
Order By: Relevance
“…In this study, a high MDS-UPDRS part 2 score was shown to be a risk factor for clinical depression and anxiety. This is consistent with previous studies suggesting that reduced exercise time was associated with worsening of both motor and non-motor symptoms under COVID-19 pandemic [ 12 14 ] and that motor fluctuation and impairment of activities of daily life were significant risk factors for the development of depression [ 26 ]. In addition, we showed that a male sex was associated with clinical anxiety, while a female sex was reported to be a potential risk factor for anxiety both in general population and in PD patients [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, a high MDS-UPDRS part 2 score was shown to be a risk factor for clinical depression and anxiety. This is consistent with previous studies suggesting that reduced exercise time was associated with worsening of both motor and non-motor symptoms under COVID-19 pandemic [ 12 14 ] and that motor fluctuation and impairment of activities of daily life were significant risk factors for the development of depression [ 26 ]. In addition, we showed that a male sex was associated with clinical anxiety, while a female sex was reported to be a potential risk factor for anxiety both in general population and in PD patients [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is becoming clear that the COVID-19 pandemic has a negative impact on the PD symptoms [ 8 , 9 , 20 ]. Van der Heide et al showed that COVID-19-related stress load was positively correlated with psychological distress, resulting in more severe PD symptoms [ 14 ]. Shalash et al showed that more than 52% of PD patients reported stress, anxiety, and disrupted contact with their physicians due to COVID-19 related social restrictions [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PD, the prevalence of depression and anxiety is substantially increased 10 , 11 , and levels of cortisol, a marker of stress, are elevated 12 , which supports the hypothesis that PD patients are especially vulnerable to effects of stress. Recently, the covid-19 pandemic served as a major stressor worldwide, and we showed in 358 PD patients that those with higher covid-19-related stressor load experienced more PD motor and non-motor symptom severity which were likely secondary to greater psychological distress as well as lifestyle changes, in particular a lack of physical activity because patients are forced to stay more inside their house to mitigate the risk of becoming infected 13 . Chronic stress might even accelerate PD disease progression, supported by PD models in rodents showing accelerated dopaminergic neuronal loss 14 and increased cerebral alphasynucleopathy after chronic stress 15 .…”
Section: Introductionmentioning
confidence: 92%